Early childhood caries and dietary habit of 4-6 years old children - Suherlan, Maudy Ahadya Putri; Suwargiani, Anne Agustina; Wihardja, Rosilawati; Kadir, Rahimah Abdul (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
AbstractIntroduction: Early childhood caries (ECC) is tooth decay commonly happened in early childhood. ECC is becoming a significant public health problem. The American Academy of Pediatric Dentistry (AAPD) encourages health care providers and caregivers to adopt preventative measures that can reduce a child's risk of developing this disease. ECC is caused by several factors, one of which is the child's diet. The prevalence of ECC in children aged 4-6 years is increasing, even though it is the age when permanent teeth start to grow. The purpose of this study was to determine the relation between ECC and dietary habit in children aged 4-6 years. Methods: The type of research is descriptive survey. The population of this study was 109 children and the sample of this study was 45 children using the purposive sampling technique and sample counting using stratified sampling. The research instruments were: odontogram medical record and Food Frequency Questionnaire form. Results: 44.45% of the children experienced ECC. The highest percentage of cariogenic food diets were snacks (48.9%), bread (42.2%), and cakes (33.3%). The highest percentage of non-cariogenic food diets were rice (93.3%), fruits (71.1%), and vegetables (40%). Conclusion: Children who experienced ECC were 44.45%. The distribution of cariogenic food diets for kindergarten students are snacks, bread, and cakes, while the highest distribution of non-cariogenic food diets are rice, fruits, and vegetables.KEY WORDSearly childhood caries, diet, cariogenic, childrenEarly Childhood caries dan pola makan anak usia 4-6 tahun: Penelitian deskriptif ABSTRAKPendahuluan: Early childhood caries (ECC) adalah kerusakan gigi pada anak anak usia dini. ECC menjadi masalah kesehatan masyarakat yang signifikan. ECC disebabkan oleh beberapa faktor, salah satunya adalah pola makan anak. Prevalensi ECC pada anak usia 4-6 tahun meningkat, padahal merupakan usia dimana gigi permanen mulai tumbuh dan berubahnya pola makan pada anak berusia 4-6 tahun. Tujuan penelitian mengetahui ECC dan pola makan kariogenik dan non kariogenik pada anak berusia 4-6 tahun. Metode: Jenis penelitian deskriptif dengan metode survei. Populasi penelitian ini berjumlah 109 anak. Sampel dari penelitian ini berjumlah 45 anak dengan menggunakan teknik purposive sampling dan penghitungan sampel menggunakan stratified sampling. Instrumen penelitian menggunakan rekam medis odontogram dan formulir Food Frequency Questionnaire. Hasil: Anak yang mengalami ECC sebanyak 44,45%. Persentase tertinggi pola makan makanan kariogenik adalah makanan ringan dalam kemasan (48,9%), roti (42,2%) dan kue (33,3%). Persentase tertinggi pola makan makanan non kariogenik adalah nasi (93,3%), buah-buahan (71,1%), dan sayuran (40%). Simpulan: Prevalensi ECC pada anak yang mengalami ECC sebanyak 44,45%. Distribusi pola makan makanan kariogenik siswa TK adalah makanan ringan dalam kemasan, roti dan kue sedangkan distribusi pola makan makanan non kariogenik tertinggi adalah nasi, buah-buahan, dan sayuran.Kata kunci: early childhood caries, diet, kariogenik, anak